Targeting Histone Deacetylases to Modulate Graft-Versus-Host Disease and Graft-Versus-Leukemia - Kim, Sena (Int J Mol Sci, 2020)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the main therapeutic strategy for patients with both malignant and nonmalignant disorders. The therapeutic benefits of allo-HSCT in malignant disorders are primarily derived from the graft-versus-leukemia (GvL) effect, in which T cells in the donor graft recognize and eradicate residual malignant cells. However, the same donor T cells can also recognize normal host tissues as foreign, leading to the development of graft-versus-host disease (GvHD), which is difficult to separate from GvL and is the most frequent and serious complication following allo-HSCT. Inhibition of donor T cell toxicity helps in reducing GvHD but also restricts GvL activity. Therefore, developing a novel therapeutic strategy that selectively suppresses GvHD without affecting GvL is essential. Recent studies have shown that inhibition of histone deacetylases (HDACs) not only inhibits the growth of tumor cells but also regulates the cytotoxic activity of T cells. Here, we compile the known therapeutic potential of HDAC inhibitors in preventing several stages of GvHD pathogenesis. Furthermore, we will also review the current clinical features of HDAC inhibitors in preventing and treating GvHD as well as maintaining GvL.